Signs of orality : the oral tradition and its influence in the Greek and Roman world - Mackay, E. Anne. (Mnemosyne, Supplements, 1999)
The essays in this volume present new insights into the far-reaching influence of an early oral culture on subsequent development after the spread of literacy. At the outset, revisionist essays on the Homeric epics examine such questions as historical memory, Homer's audience(s), descriptive strategies, ring-composition, and the status of orality as a constitutive feature of the epics. These are followed by virtually unprecedented studies of the orality of later (written) literature, including Greek oratory, Virgilian epic, Pliny's Panegyricus and story-telling in late Greek writers. Included as well are two discussions of Athenian vase-painting: annular scene-composition in the black-figure tradition, and the implications of kalos -inscriptions. An introduction by leading oral theorist John Miles Foley situates all the essays at the leading edge of oral theoretical development.